Zimbabwean War of Independence 1980-1966 (Journal of the College of Basic Education, 2023)
In the early 1960s, successive white settler regimes stood up to proposalsBritain was putting it forward to give the right to rule to the majority in Southern Rhodesia (named afterRhodesia soon before the Ian Smith regime declared Zimbabwe's illegal independence in11 November 1965 under the rule of the white minority and separation from the rule of the crownthe British (1), in the distant future.The African national leaders of that era put their trust in Britain's intentions to abandonabout colonialism, but the trust was not in its place. Britain was the authority of the colonynominal, and that it had granted the settlers internal autonomy in 1923It has reserved its right (which it has never exercised) to amend or reject any legislation established by it.settlers, so leaders like Joshua Nkomo continued(Joshua Nkomo) insisting on adopting a semi-peaceful protest methodconstitution, and focused on persuading the United Nations and friendly countries in Africa and governmentsThe other is to pressure Britain to intervene directly in Salisbury. (2)Nkomo was a former worker, social worker, trade unionist and preacher.Protestant, undisputed leader of the Zimbabwean National Movement until 1963, when(1) Boutros Boutros-Ghali, International Relations within the Framework of the Organization of African Unity, Cairo, 1974.p.398(2) Ali Ai Fru’i and Michael Tidy, Nationalism and the New States in Africa, translated by Shaker Nassif.C, 1, Baghdad, 1990, p.329